Peran Metode Failure Mode and Effect Analysis (FMEA) terhadap Mutu Pelayanan Rumah Sakit: Systematik Review - Anisa Sri Utami; Rahmi Fahmy; Zifriyanthi Minanda Putri (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
Incidence of medication errors, nosocomial infections, falling patients, pressure sores (pressure sores) is often found in hospitals. This incident can be prevented by identifying the risk and finding the root of the problem using Failure mode and effect analysis (FMEA). This study aims to describe the effectiveness of the FMEA method on the quality of hospital services using a systematic review method. This research starts from searching for data using five databases with the keywords "FMEA or Risk Management or HFMEA" and "service quality" and "hospital" then doing screenings and feasibility assessments of 17 articles. The results of this study were seventeen articles describing the FMEA method in several hospital service processes where the evaluation results of the FMEA method could improve service quality. Therefore the FMEA method is effectively applied to the service process starting from identifying the risk of failure in service, implementing preventive measures to improve the quality of hospital services in the form of security dimensions, effectiveness, and efficiency. So this study recommends the use of the FMEA method in identifying the risk of failure to improve service quality.